Składnia imiesłowów przysłówkowych uprzednich w Pamiętnikach Jana Chryzostoma Paska i w tłumaczeniu Pamiętników przez Zenona Gołaszewskiego - Kajpust, Weronika (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article is devoted to the syntax of the perfect adverbial participle in Pamiętniki (Memoirs) of Jan Chryzostom Pasek and its place in the modern Polish language. An attempt has been made to make a comparative analysis of the mentioned Old Polish work with its translation into modern Polish by Zenon Gołaszewski. With the help of a modern grammatical approach, the syntactic use of the perfect adverbial participle by Pasek was classified. In addition, the article describes what equivalents Gołaszewski used in place of these forms when he decided to make a substitution and why. The objective was to see if Pasek’s archaic use of the perfect adverbial participle can hinder the reading and reception of his work. The rather unambiguous conclusions of this analysis may be a prevailing argument in the contemporary debate on the validity of producing translations of Old Polish works into modern Polish and revising views on the reading list.